Anchoring Energy Enhancement for Plasma Alignment Technology - Hsu, Chih-Yi; Lee, Tse-Hsien; Chen, Huang-Ming Philip; Kuo, Hui-Chien J.; Chen, Yi-Fan; Lee, Chin-Yang; Lin, Yin-Chang; Hsu, Yao-Jane (My University, 2009)
The oxygen plasma post-treatment was adopted for alignment preparation in Ar plasma alignment process. The light leakage at the dark slate was suppressed by the new treatment. The NEXAFS data suggested that the out of plane carbonyl groups have been regenerated under oxygen plasma post-treatment. The polar anchoring energy was two times increased comparing to the Ar treated PI. The cell's EO properties by new plasma treatment were comparable to the rubbed PI surface.